PENGARUH PENDEKATAN CTL TERHADAP PRESTASI BELAJAR KOGNITIF MAHASISWA - Puput Wahyu Hidayat (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
The purpose study was to depcription the effect contextual teaching and learning (CTL) approach toward student learning achievement at PGSD STKIP Muhammadiyah Muara Bungo. The Research concept used quantitative research, with pretest-posttest non-equivalent group design. This Research population include all members od third semester student which has 4 classes. Meanwhile, two choosen classes made for an example of Research it was Class C and D. The results of this study indicate that the CTL approach can improve the student learning achievement is better than conventional approach.